Comparison of pharmacokinetics of tilmicosin in healthy pigs and pigs experimentally infected with Actinobacillus pleuropneumoniae. Issue 5 (3rd September 2019) - Xiong, J; Zhu, Q; Yang, S; Zhao, Y; Cui, L; Zhuang, F; Qiu, Y; Cao, J
ABSTRACT: Aim: To compare the pharmacokinetic profiles of tilmicosin, administered orally at a single dose of 20 mg/kg bodyweight, in healthy pigs and in pigs experimentally infected with Actinobacillus pleuropneumoniae . Methods: Twelve healthy crossbred pigs, aged approximately 8 weeks, were randomly assigned to uninfected and infected groups, with six pigs per group. Pigs in the infected group were inoculated intranasally with a bacterial suspension of A. pleuropneumoniae containing approximately 10 8 cfu. Each pig received a single oral dose of 20 mg/kg bodyweight of tilmicosin, given 3–4 hours after inoculation in infected pigs. Blood samples were collected before drug administration and up to 48 hours after tilmicosin administration. Concentrations of tilmicosin in plasma samples were determined by HPLC. Throughout the experimental period pigs were observed for signs of inappetence and clinical abnormalities. After sampling was complete pigs were subject to euthanasia and samples collected for gross and histopathology as well as microbiology. Results: Infected pigs showed signs of bradykinesia, nasal discharge dyspnoea, and coughing 1 hours after inoculation and A. pleuropneumoniae was cultured from the lungs of all infected pigs postmortem. Comparing pharmacokinetic parameters in uninfected and infected pigs, the maximum plasma concentration of tilmicosin was higher in uninfected pigs (1.17 (SD 0.17) vs. 0.96 (SD 0.17) µg/mL), the time to reach maximum concentration was shorter (1.53 (SD 0.23) vs. 2.40 (SD 0.37) hours), and the half-life of the absorption phase and half-life of the elimination phase were both shorter (0.66 (SD 0.08) vs. 1.00 (SD 0.27) hours) and (12.93 (SD 0.96) vs. 16.53 (SD 0.55) hours), respectively. The apparent volume of distribution was smaller in uninfected than infected pigs (1.91 (SD 0.22) vs. 2.16 (SD 0.21) L/kg). The relative bioavailability of tilmicosin in infected relative to uninfected pigs was 108.6 (SD 9.71)%. Conclusions and clinical relevance: The results of this study indicate that A. pleuropneumoniae infection significantly changed certain pharmacokinetic parameters of tilmicosin in pigs. In infected pigs tilmicosin exhibited a longer drug persistence and a better extent of absorption. These results indicate that it is necessary to monitor and adjust the dose of tilmicosin administration during the presence of pleuropneumonia. It is expected that this can optimise clinical efficacy and help avoid the development of resistance.